Treatment Evaluation with Multiple Outcome Periods under Endogeneity and Attrition - Markus Frölich; Martin Huber (Institute for the Study of Labor (IZA), 2014)
This paper develops a nonparametric methodology for treatment evaluation with multiple outcome periods under treatment endogeneity and missing outcomes. We use instrumental variables, pre-treatment characteristics, and short-term (or intermediate) outcomes to identify the average treatment effect on the outcomes of compliers (the subpopulation whose treatment reacts on the instrument) in multiple periods based on inverse probability weighting. Treatment selection and attrition may depend on both observed characteristics and the unobservable compliance type, which is possibly related to unobserved factors. We also provide a simulation study and apply our methods to the evaluation of a policy intervention targeting college achievement, where we find that controlling for attrition considerably affects the effect estimates.
Keywords: C14; C21; C23; C24; C26; 330; treatment effect; attrition; endogeneity; panel data; weighting